Linguistic relativity and second language acquisition : investigating the effect of tense on English-Chinese bilinguals’ habitual orientation to event time - Ho, Karen Xian Xi (2015)
This study expanded on the research of Chen, Su and O’Seaghdha (2013), investigating the effects of naturalistic and semi-naturalistic learning on L2 speakers’ cognition in the habitual orientation towards event time. It has been found that cross-linguistic differences in the grammatical marking of tenses can influence the conception of time. Tense-less speakers’ sensitivity to the time of an action event may be altered according to the extent of their experience with a tense language. Thus, this study looked at English-Chinese bilinguals in Singapore with both tense and tense-less language systems present within them. Experiment 1 and 2 comprised of similarity judgment and description tasks of action events with different temporal phases. Experiment 3 and 4 comprised of temporal judgment tasks that measures the participants’ estimated event span (i.e distance between imminent and completed time points) and duration. Results showed that semi-naturalistic L2 participants formed higher temporal matches, produced specific temporal descriptions and indicated a wider time window for the duration of action than naturalistic L2 participants. This suggests that semi-naturalistic L2 learners tend to focus on temporal segmentation whereas, naturalistic L2 learners who focuses more on temporal continuity. However, it was found that the degree to which L2 speakers shifted their orientation to event time towards the L2 pattern depended on their language dominance. These findings have implications for theories on L2 acquisition and bilingualism, and provide better insight on the relationship between language and cognition.